Robust Vehicle Dynamics Control for a Sharp Curve With Uncertain Road Condition - Miao, Jing; Dai, Yifan; Xie, Ou; Chen, Hao; Niu, Fuzhou; Shen, Yehu; Wu, Yong Zhi; Sun, Hui; Niu, Xuemei; Zhu, Qixin; Shen, Wenjiang (Frontiers in Energy Research, 2021)
Recently, more and more research has been conducted to develop Connected Autonomous Vehicles (CAVs) applications that ensures the safety driving of CAVs under some extreme situations. This brief presents a robust control strategy for CAVs to preserve a precise tracking performance and maintain the stability of lateral dynamics when passing a sharp curve with uncertain road friction coefficient changes. In the proposed robust lateral dynamics control, robust optimization-based lateral dynamics controller is designed to achieve the stability of the lateral dynamics with the consideration of the road friction coefficient uncertainty. Simulation validations are carried out to evaluate the proposed control strategy. The results show that the robust optimization-based lateral dynamics can improve the robustness even with the uncertainty of the road friction coefficient.